Hubungan Kadar Kreatinin dengan Durasi Pengobatan HD pada Penderita Gagal Ginjal Kronik - Shelfi Aprilia Ningsih; Hetti Rusmini; Ratna Purwaningrum; Zulfian Zulfian (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Introduction; One of the renal replacement therapies in kidney failure patients in hemodialysis (HD). The length of hemodialysis affects the serum creatinine level. Aim; knowing creatinine levels with the duration of HD treatment in patients with chronic renal failure. Method; retrospective analytic study with cross-sectional approach. The sample in this study was all serum of hemodialysis chronic renal failure patients recorded in medical record data. Data analysis used univariate analysis and bivariate analysis with the Spearman rho test. Result; It is known that the prevalence of serum creatinine levels in Chronic Renal Failure. Patients with the average creatinine level of respondents were 8.6 mg/dl with the lowest creatinine level was 4.4 mg/dl and the highest was 18.4 mg/dl, and the prevalence of HD treatment. hemodialysis treatment> 6 months as many as 43 respondents (82.7%). The results of the analysis of creatinine levels with HD treatment duration: p-value: 0.001; r: -0.464). Conclusion: There is a significant relationship between creatinine levels and the length of HD treatment in patients with chronic renal failure.